Thinking, Fast and Slow? Some Field Experiments to Reduce Crime and Dropout in Chicago - Heller, Sara B; Shah, Anuj K; Guryan, Jonathan; Ludwig, Jens; Mullainathan, Sendhil; Pollack, Harold A (The Quarterly journal of economics, 2017)
We present the results of three large-scale randomized controlled trials (RCTs) carried out in Chicago, testing interventions to reduce crime and dropout by changing the decision making of economically disadvantaged youth. We study a program called Becoming a Man (BAM), developed by the nonprofit Youth Guidance, in two RCTs implemented in 2009-2010 and 2013-2015. In the two studies participation in the program reduced total arrests during the intervention period by 28-35%, reduced violent-crime arrests by 45-50%, improved school engagement, and in the first study where we have follow-up data, increased graduation rates by 12-19%. The third RCT tested a program with partially overlapping components carried out in the Cook County Juvenile Temporary Detention Center (JTDC), which reduced readmission rates to the facility by 21%. These large behavioral responses combined with modest program costs imply benefit-cost ratios for these interventions from 5-to-1 up to 30-to-1 or more. Our data on mechanisms are not ideal, but we find no positive evidence that these effects are due to changes in emotional intelligence or social skills, self-control or "grit," or a generic mentoring effect. We find suggestive support for the hypothesis that the programs work by helping youth slow down and reflect on whether their automatic thoughts and behaviors are well suited to the situation they are in, or whether the situation could be construed differently. Codes: C91, C93, D03, D1, I24, I3, I32, K42.